Planejamento do processo de suprimento de frutas e legumes na cadeia varejista: estudo de caso e proposta de um método - Marqui, Angela Cristina (Universidade Federal de São Carlos, 2011)
ABSTRACT The basic grocery supply chain and the retailers themselves make use of practices to support management of business processes with the aim of better meeting demand requirements and/or reduced costs of the processes along the supply chain. However, by researching the management of the supply chain of more specific product categories, such as fruit and vegetables, it can be observed that there is a significant difference in management of the supply chain for these products compared to basic grocery. The differences are due to, among other factors, the particularities of the supplier market, competitiveness, and the strategic importance of fruit and vegetables for the retailers. On the other hand, products with shorter shelf life, like fruit and vegetables, require more attention on managing the order-todelivery cycle, so that the availability at point of sale is guaranteed. The lower the order-todelivery cycle, the longer the product will be available before it becomes inappropriate for commercialization. Moreover, differently to the suppliers of basic groceries, the supplier base of fruit and vegetables in a national context are characterized by low professionalization of manpower and poor management infrastructure. In this context, the objective of this project is to develop a method for planning the supply process of fruits and vegetables in retail supply chains . For this purpose it was proposed to undertake case studies in different store formats, distribution centers and first-tier suppliers. As result it is expected to analyze the differences between the categories of basic groceries and fruits and vegetables, thus showing the contextual factors that lead to the need for a method for planning the supply process of fruits and vegetables in retail supply chains. Finally, it is expected to contribute by proposing a method that takes into account such particularities. This research contributes to the theory, since it groups under-researched elements in a specific sector, the fruits and vegetables, in order to contribute to the development of the subject taking into account the Brazilian context. Beside this, it is expected that the results of this thesis contribute to the practice of retail supply chains, particularly the management of supply and distribution of fruit and vegetables items.
Keywords: Gestão de suprimentos; Gestão da cadeia de suprimentos; Comércio varejista; Ciclo do pedido; Reposição; Supply chain management; Retail; Order-to-delivery and replenishment; ENGENHARIAS::ENGENHARIA DE PRODUCAO